Estudo sobre o emprego do CAPE SEAL em revestimentos rodoviários do Estado do Ceará - Vasconcelos, Márcio Anderson Guedes (2013)
Surface treatment is one of the main bituminous wearing courses applied in flexible pavements in Brazil. This is due its use in roads with low to medium traffic volume, as well as in the conservation and preventive maintenance. Among the surface treatments, the Simple Surface Treatment (SST) and the Double Surface Treatment (DST) represent together 63% of the state roads in Ceará. Microsurfacing has increased its application in the last years. The composition of a SST as a first layer and a microsurfacing as a second one is known as Cape Seal (CS), and it has as an advantage the combination of the characteristics of these two techniques. However, there is still no application of Cape Seal in Ceará. The main objective of this research is to develop a laboratory procedure to evaluate the cape seal performance when using steel slag or mineral aggregates. The laboratory procedure developed was separated in four different procedures that began with the characterization of the materials, mix design, performance test using the Wet Track Abrasion Test, and a lab traffic simulator. The characterization results of steel slag attend the safety parameters recommended by technical specifications. The steel slag’s specimens were analyzed with the lab traffic simulator and showed better results when compared to the mineral aggregate considering surface deterioration, rutting and roughness. The results indicated the applicability of steel slag in both CS and DST. The laboratory procedure results indicated that cape seal, when compared to double surface treatment with respect to technical and economic parameters, showed a better capacity to absorb loads and presented lower deterioration. However, the cape seal's application should be carefully considered in the project’s feasibility. The results showed that cape seal is recommended to roads that require a better quality wearing course, when compared to double surface treatment.